2020
DOI: 10.1073/pnas.2004281117
|View full text |Cite
|
Sign up to set email alerts
|

Identifying collagen VI as a target of fibrotic diseases regulated by CREBBP/EP300

Abstract: Fibrotic diseases remain a major cause of morbidity and mortality, yet there are few effective therapies. The underlying pathology of all fibrotic conditions is the activity of myofibroblasts. Using cells from freshly excised disease tissue from patients with Dupuytren’s disease (DD), a localized fibrotic disorder of the palm, we sought to identify new therapeutic targets for fibrotic disease. We hypothesized that the persistent activity of myofibroblasts in fibrotic diseases might involve epigenetic modificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
50
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(55 citation statements)
references
References 74 publications
4
50
1
Order By: Relevance
“…BRD4 also marks the TSS within both promoters, again with elevated levels of H3K27 acetylation reflecting high levels of active transcription of these genes. We also performed EP300 Chip-Seq de novo motif analysis of the EP300-enriched loci and identified known consensus binding sequences for the transcription factor Fra-1/FOSL1 and subsequently confirmed a role of this TF in COL6A3 gene expression [107]. Further evidence supporting a direct role of this transcription family in the regulation of collagen VI gene expression was recently described by Ucero et al [109].…”
Section: Transcriptional Control Of Collagen VI Expressionsupporting
confidence: 67%
“…BRD4 also marks the TSS within both promoters, again with elevated levels of H3K27 acetylation reflecting high levels of active transcription of these genes. We also performed EP300 Chip-Seq de novo motif analysis of the EP300-enriched loci and identified known consensus binding sequences for the transcription factor Fra-1/FOSL1 and subsequently confirmed a role of this TF in COL6A3 gene expression [107]. Further evidence supporting a direct role of this transcription family in the regulation of collagen VI gene expression was recently described by Ucero et al [109].…”
Section: Transcriptional Control Of Collagen VI Expressionsupporting
confidence: 67%
“…Therefore collagen VI deposition in ageing and disease may occur to restore the mechanical properties of the GBM. Furthermore, collagen VI is a prominent downstream regulator of myofibroblast activity, with knockdown reducing fibrosis (46). Our data shows collagen VI increasing early where it may act to strengthen BM defects while paradoxically promoting fibrosis (Figure 8E).…”
Section: Discussionmentioning
confidence: 68%
“…The compound has been suggested to reduce fibrosis because it either directly or together with an inhibitor of the main collagen receptor discoidin domain receptor 1 (DDR1) attenuated lung inflammation and fibroblast activation in idiopathic pulmonary fibrosis [ 81 , 87 ]. In addition, a transcriptome analysis found that multiple pro-fibrotic pathways were dysregulated in CBP30-treated myofibroblasts derived from patients with Dupuytren’s disease [ 88 ]. As to be expected, CBP30 reduced the overall H3K27ac level and the radiation-induced expression of DGKA and collagens in BJ fibroblasts.…”
Section: Discussionmentioning
confidence: 99%